2018
DOI: 10.1161/circoutcomes.118.004829
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation in the Utilization and Implementation of Targeted Temperature Management in Out-of-Hospital Cardiac Arrest

Abstract: Background Targeted temperature management (TTM) for out-of-hospital cardiac arrest is associated with improved functional survival and is a class I recommendation in resuscitation guidelines. However, patterns of utilization of TTM and adherence to recommended TTM guidelines in contemporary practice are unknown. Methods and Results In a multicenter, prospective cohort of consecutive adults with non-traumatic out-of-hospital cardiac arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In the USA, where this treatment was historically less employed as compared with European countries, TTM use was shown to further decrease in many centers, as revealed by recent administrative data [8]. In parallel, Khera et al found that TTM use dropped in all subgroups of CA survivors (both shockable and non-shockable) [9]. On the whole, these uncertainties prompted to perform new large randomized trials testing this treatment in CA patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, where this treatment was historically less employed as compared with European countries, TTM use was shown to further decrease in many centers, as revealed by recent administrative data [8]. In parallel, Khera et al found that TTM use dropped in all subgroups of CA survivors (both shockable and non-shockable) [9]. On the whole, these uncertainties prompted to perform new large randomized trials testing this treatment in CA patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, substantial variation has been shown in post-resuscitation care across hospitals including targeted temperature management. 11,34 It is unclear to what extent differences in post-resuscitation care exist in Denmark, and whether hospital-level variation in outcomes will decrease as potential disparities in resuscitation care are diminished. Additional research is warranted to inform on hospital-level variation in resuscitation care and its influence on variation in outcomes after IHCA in Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, excellence in post-resuscitation care among patients who survive the acute resuscitation likely plays a large role, [22][23][24][25][26] given wide variations in post-resuscitation expertise across hospitals. [27][28][29][30][31][32] This is a critical issue with the current award system for inhospital cardiac arrest, as the process-of-care measures which comprise the award measure relate to best practices for conducting acute resuscitation but do not capture excellence in the delivery of post-resuscitation care in intensive care units among patients who achieve ROSC. Finally, hospital systems for resuscitation care may play a large role in higher facility-level survival rates for in-hospital cardiac arrest, 30 and these unmeasured factors include a focus on hospital culture towards iterative quality improvement in resuscitation performance, organized care teams, experienced and motivated staff, recurrent training and frequent use of resuscitation simulations, and a non-threatening method to assess system failures.…”
Section: Discussionmentioning
confidence: 99%